2021
DOI: 10.1097/mph.0000000000002268
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis-Associated Aplastic Anemia: Etiology, Clinical Characteristics and Outcome

Abstract: Hepatitis-associated aplastic anemia (HAA) is a form of acquired aplastic anemia (AA) in which bone marrow failure develops after an acute attack of hepatitis. Bone marrow failure leading to AA is generally severe in cases of HAA and fatal if left untreated. This retrospective multicenter study investigated clinical and laboratory characteristics, possible causes, treatment, and outcome of HAA in children. Twenty patients from 8 centers were included in the study. Aspartate aminotransferase and alanine aminotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…According to standardised protocols, all patients were considered for allogeneic hematopoietic stem cell transplantation, which was available only in 1 patient. The other 5 patients were treated with immunosuppressive therapy; at last follow up they are alive and well [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to standardised protocols, all patients were considered for allogeneic hematopoietic stem cell transplantation, which was available only in 1 patient. The other 5 patients were treated with immunosuppressive therapy; at last follow up they are alive and well [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, in this cohort, 16% of patients with ID-ALF (all included in G2) developed AA by 90 days after the diagnosis of ALF. Aplastic anaemia was diagnosed by bone marrow biopsy in all (100%), and it was classified as severe AA according to the standard classification [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various immune mechanisms triggered by various acute insult have been elucidated as the cause of bone marrow failure following an episode of severe acute hepatitis. These include increased activation and a broad skewing pattern of T cell fractions such as circulating cytotoxic T cells which infiltrate and accumulate in the liver (with notable inflammation on liver biopsy), defective monocyte to macrophage differentiation, CD8+ Kupffer cell-mediated liver and bone marrow toxicity, increase in interferon-gamma and interleukin-2-mediated organ damage in liver and bone marrow—all of which are driven by hapten/antibody-mediated inflammatory cascade after the initial insult 16 17. Similar immune mechanisms, immune dysfunction and adaptive and innate immune changes (direct or indirect toxicity due to antibody or secondary metabolite generation) have been described in DILI, possibly explaining common pathophysiological mechanisms that result in HAAA syndrome development 18–20.…”
Section: Discussionmentioning
confidence: 99%
“…The virus begins to block host macromolecular synthesis and mRNA transport to the cytoplasm after many replication cycles. These cellular disruptions damage host cells and may produce symptoms of disease in their hosts, such as respiratory stress [ 35 ]. Studies have suggested that the penton protein of adenoviruses seems to be virulent, in addition to the symptoms caused by cell lysis and the inhibition of cellular synthesis.…”
Section: Hepatitismentioning
confidence: 99%